2014
DOI: 10.1002/2014ja020089
|View full text |Cite
|
Sign up to set email alerts
|

First U.S.‐China joint ground‐based Fabry‐Perot interferometer observations of longitudinal variations in the thermospheric winds

Abstract: For the first time, three Fabry-Perot interferometers from the U.S. (Boulder, 40°N, 105°W, 49°N magnetic latitude (MLAT)) and China (Xinglong: 40°N,115°E, 34°N, MLAT; Kelan: 39°N, 112°E, 33°N MLAT) were used to examine the longitudinal variations in the thermospheric winds due to the geomagnetic latitude differences between the American and Asian sectors. During a case of quiet geomagnetic condition, the meridional winds were very similar at the U.S. and Chinese stations. The meridional winds at Boulder rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 23 publications
4
30
0
Order By: Relevance
“…For the zonal winds, differences were seen in the amplitude of the maximum eastward flow (with the winds typically being faster over Morocco) as well as the timing of the reversal from eastward to westward flow (with the reversal taking place 2 h earlier in local time over PARI). Fisher et al (2015) concluded that, in line with the prior hypothesis presented by Wu et al (2014), some of these differences were likely attributable to differences in the geomagnetic latitudes of the two sites. This prompts the need to compare the data from Oukaïmeden with data from a site at a similar geomagnetic latitude.…”
Section: Comparison To Prior Observationsmentioning
confidence: 60%
“…For the zonal winds, differences were seen in the amplitude of the maximum eastward flow (with the winds typically being faster over Morocco) as well as the timing of the reversal from eastward to westward flow (with the reversal taking place 2 h earlier in local time over PARI). Fisher et al (2015) concluded that, in line with the prior hypothesis presented by Wu et al (2014), some of these differences were likely attributable to differences in the geomagnetic latitudes of the two sites. This prompts the need to compare the data from Oukaïmeden with data from a site at a similar geomagnetic latitude.…”
Section: Comparison To Prior Observationsmentioning
confidence: 60%
“…The Kelan FPI system (geographically 38.7°N, 111.6°E; geomagnetically 34°N; Figure ) has a similar design to the FPI deployed at XL (Wu et al, ). Three wavelengths of nightglow at 892.0, 557.7, and 630.0 nm are observed with the integration time of 3, 3, and 5 min, respectively.…”
Section: Fpi Instruments Models and Data Analysismentioning
confidence: 99%
“…Recently, Wu et al (2014) compared simultaneous TW observations made in China and the United States (US) for two cases in October, and pointed out that Vn during low geomagnetic activities (Kp ~ 2) shows different characteristics before midnight (LT), although they show similar characteristics for Ve during low geomagnetic activities and for Vn and Ve during quiet geomagnetic condition (Kp ~ 1). The diurnal cycle of TWs over Asia-Oceania may differ from that in the Western Hemisphere, and the relationship should depend on the geomagnetic conditions.…”
Section: Climatology Of Shigarakimentioning
confidence: 99%
“…The climatological TWs are dependent on the geographical latitude, season, and solar activity (e.g., Emmert et al 2006a). In addition, the TWs may not be longitudinally symmetric; i.e., magnetic discrepancy between geomagnetic and geographic coordinates and nonmigrating tide can cause change in the TWs (Wu et al 2014). One example of geographical-longitudinal dependency of TWs is the wave-4 structure observed in the equatorial ionosphere and thermosphere (e.g., Immel et al 2006).…”
Section: Introductionmentioning
confidence: 99%